2021
DOI: 10.1002/hbm.25558
|View full text |Cite
|
Sign up to set email alerts
|

Characterizing white matter alterations subject to clinical laterality in drug‐naïve de novo Parkinson's disease

Abstract: Parkinson's disease (PD) is a progressive neurodegenerative disorder that is characterized by a range of motor and nonmotor symptoms, often with the motor dysfunction initiated unilaterally. Knowledge regarding disease‐related alterations in white matter pathways can effectively help improve the understanding of the disease and propose targeted treatment strategies. Microstructural imaging techniques, including diffusion tensor imaging (DTI), allows inspection of white matter integrity to study the pathogenesi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
24
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(30 citation statements)
references
References 39 publications
4
24
0
Order By: Relevance
“…Hence our results regarding fibre density should be interpreted with the necessary care. However, we also highlight that our results regarding the fibre density can be deemed pathophysiologically plausible and that previous FBA-based analyses with a b-value of 1000 s/mm 2 also came to conclusive results 42 , 43 . Also, the effects of lower b-values should be attenuated by the application of single-shell 3-tissue constrained spherical deconvolution during processing in our analysis.…”
Section: Discussionsupporting
confidence: 78%
See 2 more Smart Citations
“…Hence our results regarding fibre density should be interpreted with the necessary care. However, we also highlight that our results regarding the fibre density can be deemed pathophysiologically plausible and that previous FBA-based analyses with a b-value of 1000 s/mm 2 also came to conclusive results 42 , 43 . Also, the effects of lower b-values should be attenuated by the application of single-shell 3-tissue constrained spherical deconvolution during processing in our analysis.…”
Section: Discussionsupporting
confidence: 78%
“…Of note, our b-value of b = 1000 s/mm 2 is smaller than the recommendation for quantifying FD 21 . However, our approach follows previous studies yielding plausible results based on single-shell data with b = 1000 s/mm 2 42 , 43 . Fibre-bundle cross-section (FC) measures differences in fibre-bundle diameters between a subject’s FOD and the FOD template.…”
Section: Methodsmentioning
confidence: 86%
See 1 more Smart Citation
“…Using the traditional method, we have largely reproduced the results generated by the voxel-based analysis performed by Xiao et al (2021), specifically in terms of the white matter bundle extending from the cortex to the brain stem on the collateral to symptom onset. This validates that the statistical mapping method used for all three approaches is coherent with the literature.…”
Section: Cnn Sensitivity At Specific Regionsmentioning
confidence: 89%
“…On the PPMI dataset (Marek et al, 2011) significant alterations between healthy controls and Parkinsonian patients located within the SN, the striatum and the subthalamic nucleus (STN), pallidum, putamen and thalamus have been previously reported (Schuff et al, 2015;Cousineau et al, 2017). Xiao et al (2021) have also found significant differences in the major white matter bundles between patients and controls specifically on the side of PD onset.…”
Section: Diffusion Tensor Imaging In Parkinson's Diseasementioning
confidence: 99%